Acupuncture Reduced the Risk for Insomnia in Stroke Patients: A Propensity-Score Matched Cohort Study - Qiu, Xuan; Han, Nan Sheng; Yao, Jie Xiao; Yu, Fang Rui; Lin, Yan Yan; Zhuang, Xun (Frontiers in Aging Neuroscience, 2021)
Background: Post-stroke insomnia (PSI) affects the quality of life for stroke patients, reduces the likelihood of successful rehabilitation, and produces additional complications following stroke. Previous reports have provided some information regarding PSI risk factors, but little is known concerning protective factors for PSI. This study analyzed the relationship between acupuncture and insomnia in stroke patients and explored the use of acupuncture as a preventive treatment. Methods: Patients diagnosed with stroke from 2010 to 2019 were identified in the case database of the First Affiliated Hospital of Guangzhou University of Chinese These patients followed until 2020, and numerous factors were examined, including gender, age, stroke type, stroke location, and baseline comorbidities. A 1:1 propensity score was used to match an equal number of patients receiving acupuncture with stroke patients who did not receive acupuncture (N = 1,680 for each group). The purpose of the study was to compare the incidence of insomnia in these two stroke cohorts. We used the Cox regression model and Kaplan-Meier method to estimate the risk of insomnia as the outcome event. Results: Compared with the non-acupuncture cohort in general, stroke patients who received acupuncture treatment exhibited a lower risk of insomnia after adjusting for age, gender, stroke type, stroke location, and comorbidities (adjusted hazard ratio HR = 0.27, 95% confidential interval = 0.23 to 0.32). Acupuncture also reduced the risk of PSI for both genders. The respective risks were HR = 0.28 (adjusted) for males and HR = 0.26 (adjusted) for females. Acupuncture also lowered the risk for PSI for different age groups. The risks were HR = 0.22 (adjusted) for individuals 18 to 39 years of age, HR = 0.31 (adjusted) for individuals 40 to 59 years of age, HR = 0.28 (adjusted) for those 60 to 79 years of age, and HR = 0.18 (adjusted) for individuals 80 years of age and older. Concerning the stroke type, regardless of whether the stroke was ischemic, hemorrhagic, or a combination of the two stroke types, patients who received acupuncture exhibited lower risk (adjusted HR = 0.28, 0.17, and 0.49, respectively). Concerning stroke location, except for the cerebral hemispheres (adjusted HR = 1.10, 95% confidential interval = 0.12 to 1.01), the risk of PSI after receiving acupuncture was lower for the frontal lobe (adjusted HR = 0.42), the basal ganglia (adjusted HR = 0.22), the radiation crown (adjusted HR = 0.42), the diencephalon (adjusted HR = 0.20), or multiple partial strokes (adjusted HR = 0.26), the risk of PSI after receiving acupuncture was lower. For all baseline complications, acupuncture reduced the risk of insomnia. The cumulative incidence of insomnia in the acupuncture cohort was significantly lower than the non-acupuncture cohort (log-rank test, P = 0.000). Limitations: First, our research only included patients from a single center. Second, we did not classify the post-stroke insomnia severity. Second, the information was extracted manually. Overall, the sample size was small, and we needed to increase the sample size to strengthen the conclusions. Conclusion: Acupuncture treatment reduced the risk of insomnia in stroke patients. Future research be conducted with increased sample sizes and further elaboration on the specific acupuncture protocols that were used.